Ibn Khaldun's 'ilm al 'umran: a model for planning the sustainable city in the Arab region. (15th July 2019) - El-Kholei, Ahmed O.
Abstract : Purpose: Sustainable development is an attempt to achieve three competing aims: economic development, social justice and environmental conservation. Localising sustainable development in the Arabian city might require a framework that originates from its reality manifested in the region's history, culture and religion. Ibn Khaldun's model seems suitable for planning a sustainable city in the Arab world. The purpose of this paper is to discuss suitability of Ibn Khaldun's writing to localising sustainable development in the Arabian cities. Design/methodology/approach: The paper used a qualitative research methodology. The researcher investigated the writings of Ibn Khaldun and other scholars who studied his work to derive lessons for planning the sustainable Arab city. Findings: Many of Ibn Khaldun's concepts lost their accuracy, meanings and intentions in the course of translating his work. Ibn Khaldun's writings can be the source from which scholars, planners and city administrators derive lessons to assure the sustainable development of human settlements, particularly in the Arab region. The writings of Ibn Khaldun are relevant to the Arab countries. His writings are sensitive to the realities of the Arab world, including geography, environment, history, religion and culture. His writings can support efforts for localising sustinable development in the Arabian cities. Originality/value: Interrogating Ibn Khaldun's writings can enable scholars, planners, architects and city administrators to elaborate and implement plans for the sustainable Arabian city. The findings of the paper assure that Ibn Khaldun's analysis is suitable for addressing the urban ills of the contemporary Arabian metropolis as they were in his time.